Floristic and phytosociology of the herbaceous/shrub stratum in 19 areas of Amazonian savannas, Brazil - da Rocha, Antônio Elielson Sousa; da Costa Neto, Salustiano Vilar (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
The present study aims to evaluate the composition and structure of the herbaceous/shrub stratum in Amazonian savannas, in order to discuss the floristic similarity among 19 areas in the states of Amazonas, Amapá, Pará and Roraima. For the survey, 120 plots of 1m2 per area were allocated. We sampled 390 species, 203 genera, and 64 families. The analyzes point to significantly different floristic compositions. The nearby areas were more floristically similar, decreasing as the distance between them increased, with a set of endemic or exclusive species and areas with their own individualities, which implies a high specificity of this vegetation. Several factors may be influencing the floristic distinction of the areas, which makes it necessary to expand studies of the environmental conditions of this vegetation in order to better understand it.